Press Reports about Causes of Juvenile Crime and Associated Claims in the German Press - Reichert, Frank (International Journal of Criminology and Sociology, 2013)
This article examines the kinds of criminological knowledge and information that were considered in the press during the Hesse election campaign in 2007/2008, in which youth crime played a major role. The present study investigates the integration of information about the possible causes of youth crime into press articles, and examines to which extent information about these causes and motives for engaging in youth crime were considered by the press to be significant in the explanation of youth crime. The other aim of this study is to uncover which types of criminal policy and pedagogy had been reported about, and which of those measures had been regarded as meaningful. To this end, results of a content analysis of articles from two German daily newspapers—the Bild and the Süddeutsche Zeitung—are presented and compared. The differences between the two newspapers and their method of news construction are highlighted. The paper clarifies central concepts and discusses previous research in media crime and youth crime, as well as making methodological remarks. The results of the study indicate that only rarely was knowledge about the causes of juvenile crime published in the press; information about the individual itself was found to an even lesser extent. This was particularly true about the Bild. Claims for tougher methods of punishment dominated, whereas measures that aimed at crime prevention were seldom considered reasonable, and if so, were mainly included in the Süddeutsche Zeitung. These results in part reflect the importance of several news factors—notably consonance, personification, risk, and negativism—but also to a large extent reflect the political accentuation of the respective newspapers and their specific views of juvenile offenders.